Feeling otherwise: Ambivalent affects and the politics of critique in geography. Issue 1 (March 2021) - Ruez, Derek; Cockayne, Daniel
Scholars across the social sciences and humanities have increasingly questioned the meaning and purpose of critique. Contributing to those conversations, some geographers have advocated for affirmative or reparative practices such as reading for difference or experimentation that seek to provoke more joyful, hopeful, or enchanting affects, as alternatives to what they perceive as a prevailing forms of 'negative' critique. In response, others have re-emphasized the centrality of negativity and revalued negative affects in the context of regimes of racialization, heteronormativity, and coloniality. Rather than taking sides in a debate thus framed, this article develops an ambivalent position that foregrounds multiple senses of difference that exist within affirmative and reparative projects. Drawing on feminist and queer geographic work, the explicitly political and difference-oriented writing of Sedgwick and Deleuze, and queer and postcolonial affect scholars, we argue for critique characterized by an ambivalent and pluralistic attitude toward feeling. Joining those arguing for a pluralization of the moods and modes of critical work, our readings suggest the necessity of a pluralism that refuses any escape from the 'negativity' of the social field in favor of an affectively ambivalent engagement with the inherent politics of critique in a plural and uneven world.